A calcium-binding protein, rice annexin OsANN1, enhances heat stress tolerance by modulating the production of H2O2. (17th June 2015) - Qiao, Bei; Zhang, Qian; Liu, Dongliang; Wang, Haiqi; Yin, Jingya; Wang, Rui; He, Mengli; Cui, Meng; Shang, Zhonglin; Wang, Dekai; Zhu, Zhengge
Highlight: OsANN1 is Ca 2+ -dependent phospholipid-binding protein which is involved in heat and drought stress responses through its abilities to modulate the levels of H2 O2 and redox homeostasis. Abstract: OsANN1 is a member of the annexin protein family in rice. The function of this protein and the mechanisms of its involvement in stress responses and stress tolerance are largely unknown. Here it is reported that OsANN1 confers abiotic stress tolerance by modulating antioxidant accumulation under abiotic stress. OsANN1 -knockdown [RNA interference (RNAi)] plants were more sensitive to heat and drought stresses, whereas OsANN1 -overexpression (OE) lines showed improved growth with higher expression of OsANN1 under abiotic stress. Overexpression of OsANN1 promoted SOD (superoxide dismutase) and CAT (catalase) activities, which regulate H2 O2 content and redox homeostasis, suggesting the existence of a feedback mechanism between OsANN1 and H2 O2 production under abiotic stress. Higher expression of OsANN1 can provide overall cellular protection against abiotic stress-induced damage, and a significant accumulation of OsANN1–green fluorescent protein (GFP) signals was found in the cytosol after heat shock treatment. OsANN1 also has calcium-binding and ATPase activities in vitro, indicating that OsANN1 has multiple functions in rice growth. Furthermore, yeast two-hybrid and bimolecular fluorescence complementation (BiFC) assays demonstrated that OsANN1 interacts with OsCDPK24. This cross-talk may provide additional layers of regulation in the abiotic stress response.